Ecology in modern Kazakh poetry (Herald of Journalism, 2016)
The article deals with the topical problems of out modern world related to the ecological aspects of its life, and their representation in Kazakh poetry. The author pointed out that the inherent analysis of the ecological problemin the certain text results in intermittence and fragment perception instead of holistic approach to the topic. In accordance with the main idea of the article, the most productive way is to study this range of problems as ahypertext. According to that principle, all texts related to the problem mentioned before, should be considered as a «hyper-problem» which allows us to treat the peculiarities of its artistic presentation.
Keywords: ecological problem; ecological poetry; protagonist; ecological scenery; ecological culture; Aral tragedy